A Universe Designed for Life? - Holder, Rodney D. (Zygon: Journal of Religion & Science, 2025)
Why are the laws of nature so special ("fine-tuned") that the universe gives rise to intelligent creatures like ourselves, who can observe it and discover those laws? Is there really anything to explain, given that, if this were otherwise, we would not be here to pose the question? Can some better theory (a theory of everything?) do what is required by calculating the constants, so removing all free parameters from the equations? Alternatively, can the existence of a multiverse, a vast or infinite collection of universes, explain the specialness of this universe? Or, in the light of discoveries in modern cosmology, can we still speak of a divine mind behind the creation? These are the questions explored in this article.